Eleanor Oliphant is completely fine [compact disc, unabridged] : a novel - Honeyman, Gail (Penguin Audio, 2017)
A socially awkward, routine-oriented loner teams up with a bumbling IT guy from her office to assist an elderly accident victim, forging a friendship that saves all three from lives of isolation and secret unhappiness.